Portfolios across the EFL curriculum: methodological perspectives of their use in university settings - Viáfara González, John J.; López, María Eugenia (Colombian Applied Linguistics Journal, 2011)
This article emerges from the experience that two EFL university professors have accumulated for several years working with portfolios in tertiary education. Starting from the theoretical principles they have undertaken to guide their practices when using portfolios, they share their methodological procedures for ESP (English for Specific Purposes), academic literacy and teaching practicum courses. The authors describe in detail how portfolios are structured in each setting, enhancing autonomous and collaborative learning as well as the reflective teaching of the foreign language. In addition, the manuscript discusses the benefits students perceive portfolios bring since they can approach their literacy development as a process, be more creative as learners and prospective teachers, find meaningful contexts to learn and increase their metacognitive skills, among others. The pedagogical implications involve suggestions in regards to how role dynamics and power relations built around these artifacts, the need for suitable peer monitoring structures and for the creation of solid pedagogical frameworks to encourage autonomy.